2014
DOI: 10.1007/s10661-014-4100-3
|View full text |Cite
|
Sign up to set email alerts
|

Field dissipation of trifloxystrobin and its metabolite trifloxystrobin acid in soil and apples

Abstract: The dissipation of trifloxystrobin and its metabolite trifloxystrobin acid in apples and soil was studied, and the half-life (DT₅₀) was estimated in a field study carried out at three different locations for apples and four different locations for soil. Trifloxystrobin was sprayed on apples at 127 g a.i./ha for the dissipation study. Samples of apple and soil for the dissipation experiment were collected at time intervals of 0, 1, 3, 7, 14, 21, 30, and 45 days after treatment. The quantification of residues wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Since then, strobilurin fungicides have taken an important position in pesticide chemistry and become one of the most important classes of fungicides due to their stronger biological activities and lower toxicity (Gullino et al 2002;Wang et al 2015). Strobilurin is a group of agricultural fungicides for its unique mechanism, good environmental compatibility, and actual application to improve crop yield and quality (de Souza et al 2009;Xu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, strobilurin fungicides have taken an important position in pesticide chemistry and become one of the most important classes of fungicides due to their stronger biological activities and lower toxicity (Gullino et al 2002;Wang et al 2015). Strobilurin is a group of agricultural fungicides for its unique mechanism, good environmental compatibility, and actual application to improve crop yield and quality (de Souza et al 2009;Xu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the dissipation of difenoconzole in apple and soil samples from different sites in China (Xiaoxian [Anhui province], Daxing [Beijing] and Hangzhou [Zhejiang province]) had been studied. The half‐lives of difenoconazole in apples and soils were 6.3–10.2 and 9.6–68.4 days, respectively (Wang et al, ). Studies on the similarity mixture fungicides, trifloxystrobin and tebuconzole (75%, WG) residue behavior in gherkin and mango fruit had indicated that the residue of trifloxystrobin and tebuconzole in different matrices fitted with the first‐order kinetics model (Guo et al, ; Mohapatra, ).…”
Section: Resultsmentioning
confidence: 99%
“…There are previous reports on the dissipation pattern and final residues of difenoconazole and trifloxystrobin in some other matrices, such as rice (Cao et al, 2015;Chen et al, 2014;Li, Wang, Hao, & Han, 2014), tomato (Kong et al, 2012;Wang et al, 2014), apple (Guo, Li, Guo, & Wang, 2010;Wang, Wu, Zhang, Wang, & Zhang, 2015) and many other principal fruits and vegetables (Banerjee, Oulkar, Patil, Dasgupta, & Adsule, 2008;Liu et al, 2011;Mohapatra, 2015;Park et al, 2007). In previous papers, trifloxystrobin was determined by HPLC (Likas & Tsiropoulos, 2014;Zhu, Dai, Fang, & Zhu, 2013), GC with electron capture (Likas, Tsiropoulos, & Miliadis, 2007) or GC with MS (Paramasivam et al, 2015), while determination of difenoconazole was mainly developed by GC (Guo et al, 2010) and UPLC-MS/MS (Kong et al, 2012).…”
Section: Difenoconazole a Systemic Sterol Demethylation Inhibitor Bmentioning
confidence: 99%
“…However, photolysis is a major dissipation factor for TFS. To reduce the risk from TFS, application of TFS during a period of sunshine is suggested (C. Wang, Wu, Zhang, Wang, & Zhang, ). Trifloxystrobin acid (TFSA) is the main metabolite of TFS.…”
Section: Introductionmentioning
confidence: 99%
“…The overall average recoveries were from 74.2 to 107.4% with RSDs of <7.8%. C. Wang, Wu, et al () established a dispersive solid‐phase extraction method for purification and an LC–MS/MS method for the determination of TFS and TFSA in apples and soil. The determination coefficients ( R 2 ) were >0.99, and the LOD and LOQ values were 5.0 × 10 −3 ng and 10 μg/kg, respectively.…”
Section: Introductionmentioning
confidence: 99%